Analisis SWOT Dalam Meningkatkan Daya Saing PT. Pos Persero Indonesia Di Kota Palangka Raya - Rofika Sri Wulandari; Revnussa Oktobery; Kharisma Nugraha Putra; Tonich Uda; Alexandro, Rinto (FKIP, Universitas Palangka Raya, 2025)
SWOT analysis has a very important role for companies to find out what strategies will be appropriate and can be carried out by the company so that it can compete with similar companies. The purpose of this research is to determine and analyze the strategy of PT POS Persero Indonesia in Palangka Raya City in increasing the company's competitiveness based on SWOT Analysis. This research uses a qualitative method by taking a case study approach, the informants in this research are Post Office Managers, Post Office Employees, and Palangka Raya Post Office Customers. Data sources were obtained from primary data, namely from observations in the field and interviews with informants, and secondary data from documentation of the results of observations and interviews. The data analysis method uses Miles and Huberman's interactive model analysis of 3 activity stages, namely reducing data, presenting data, and drawing conclusions. Based on the results of the Grand Strategy Matrix analysis, it shows that PT Pos Indonesia Palangka Raya City is in quadrant III, namely the Turn Around and Liquidation strategy quadrant. The right strategy is the WO strategy. The WO strategy focuses on minimizing weaknesses by taking advantage of opportunities, such as collaboration with local governments and human resource training. This strategy can increase the competitiveness of PT Pos Indonesia Palangka Raya City.